Applying human mobility and water consumption data for short-term water demand forecasting using classical and machine learning models. Issue 1 (2nd January 2020) - Smolak, Kamil; Kasieczka, Barbara; Fialkiewicz, Wieslaw; Rohm, Witold; Siła-Nowicka, Katarzyna; Kopańczyk, Katarzyna
ABSTRACT: Water demand forecasting is a crucial task in the efficient management of the water supply system. This paper compares classical and adapted machine learning algorithms used for water usage predictions including ARIMA, support vector regression, random forests and extremely randomized trees. These models were enriched with human mobility data to improve the predictive power of water demand forecasting. Furthermore, a framework for processing mobility data into time-series correlated with water usage data is proposed. This study uses 51 days of water consumption readings and over 7 million geolocated mobility records from urban areas. Results show that using human mobility data improves water demand prediction. The best forecasting algorithm employing a random forest method achieved 90.4% accuracy (measured by the mean absolute percentage error) and is better by 1% than the same algorithm using only water data, while classic ARIMA approach achieved 90.0%. The Blind (copying) prediction achieved 85.1% of accuracy.